Characterization of the Chloroplast Genome Sequence of Acer miaotaiense: Comparative and Phylogenetic Analyses - Jiantao Zhao; Yao Xu; Linjie Xi; Junwei Yang; Hongwu Chen; Jing Zhang (Molecules, 2018)
Acer miaotaiense is an endangered species within the Aceraceae family, and has only a few small natural distributions in China’s Qingling Mountains and Bashan Mountains. Comparative analyses of the complete chloroplast genome could provide useful knowledge on the diversity and evolution of this species in different environments. In this study, we sequenced and compared the chloroplast genome of Acer miaotaiense from five ecological regions in the Qingling and Mashan Regions of China. The size of the chloroplast genome ranged from 156,260 bp to 156,204 bp, including two inverted repeat regions, a small single-copy region, and a large single-copy region. Across the whole chloroplast genome, there were 130 genes in total, and 92 of them were protein-coding genes. We observed four genes with non-synonymous mutations involving post-transcriptional modification (matK), photosynthesis (atpI), and self-replication (rps4 and rpl20). A total of 415 microsatellite loci were identified, and the dominant microsatellite types were composed of dinucleotide and trinucleotide motifs. The dominant repeat units were AT and AG, accounting for 37.92% and 31.16% of the total microsatellite loci, respectively. A phylogenetic analysis showed that samples with the same altitude (Xunyangba, Ningshan country, and Zhangliangmiao, Liuba country) had a strong bootstrap value (88%), while the remaining ones shared a similar longitude. These results provided clues about the importance of longitude/altitude for the genetic diversity of Acer miaotaiense. This information will be useful for the conservation and improved management of this endangered species.